2019
DOI: 10.3390/j2040027
|View full text |Cite
|
Sign up to set email alerts
|

SWOT Analysis of Blended Learning in Public Universities of Uganda: A Case Study of Muni University

Abstract: With the fusion of information communication technology (ICT) in higher institutions of learning, new teaching and learning practices have developed—often called blended learning—allowing students and teachers to interact with information and each other more independently. This study, therefore, analyses the strengths, weaknesses, opportunities and threats (SWOT) of blended learning in the Public Universities of Uganda, in a case study of Muni University. Descriptive survey design was employed in the research.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…a digital ecosystem of discussions can be constructed, between people with similar interests, in order to share knowledge, thoughts, questions and experience (Persico et al, 2014 ; Tsiotakis & Jimoyiannis, 2016 ). Discussions are stimulated outside the classroom among students and teachers, making the class more interactive and productive through pre-work (Ali et al, 2019 ).…”
Section: Swot Analysis Of Online Learning and The Particular Case Of The Mathe Environmentmentioning
confidence: 99%
See 2 more Smart Citations
“…a digital ecosystem of discussions can be constructed, between people with similar interests, in order to share knowledge, thoughts, questions and experience (Persico et al, 2014 ; Tsiotakis & Jimoyiannis, 2016 ). Discussions are stimulated outside the classroom among students and teachers, making the class more interactive and productive through pre-work (Ali et al, 2019 ).…”
Section: Swot Analysis Of Online Learning and The Particular Case Of The Mathe Environmentmentioning
confidence: 99%
“…Discussions are stimulated outside the classroom among students and teachers, making the class more interactive and productive through pre-work (Ali et al, 2019).…”
Section: Strengthsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study assessing blended learning, Ali, Buruga and Habibu (2019) did a SWOT analysis in public universities in Uganda, and reported that the blended learning had strengths in serving multiple students in a short duration, university preparation, connecting students both in and out of class, using basic skills IT and commitment from top management. Weaknesses identified from the study comprised unreliable internet, low/inadequate bandwidth, lack of plagiarism methods, scarce numbers of computers and poor internet access.…”
Section: Introductionmentioning
confidence: 99%
“…3. SWOT-analysis, various aspects of its application in education are identified, for example, in the works (Satria and Shahbana, 2020) and (Ali al., 2019).…”
Section: Introductionmentioning
confidence: 99%